XRF data of D. striatus and W. britannica at 17 keV - Baptiste Suchéras-Marx; Fabienne Giraud; Isabelle Daniel; Camille Rivard; Marie-Pierre Aubry; Karl-Heinz Baumann; Luc Beaufort; Rémi Tucoulou; Alexandre Simionovici (PANGAEA, 2020)
The data were generated at ESRF beamline ID22 with an incident energy at 17 keV. Discorhdabus striatus and Watznaueria britannica were analyzed with 0.1 μm x 0.1 μm pixel size and 2 s time analysis per pixel. Both coccoliths were picked from samples from Murtinheira section at Cabo Mondego, Portugal. D. striatus is from sample CM9 and W. britannica from sample CM60 both dated to the lower Bajocian (Middle Jurassic). Sample position in the section in Suchéras-Marx et al. (2012). Data treatment is made using PyMCA. For each calcareous nannofossil, the raw data (.edf in .zip) and the pondered spectrum (.csv) are given. One fit file is given (.cfg) and can be used for both sample. Those data were acquired through the project EC811 at ESRF. Similar results published in Suchéras-Marx et al. (2016).